At Westonci.ca, we connect you with the answers you need, thanks to our active and informed community. Connect with a community of experts ready to provide precise solutions to your questions on our user-friendly Q&A platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.

Find the sum of 3x + y , - 4x -2y

Sagot :

Answer:

(-x-y)

Step-by-step explanation:

Given data

First expression = ( 3x + y)

Second expression = (-4x -2y)

Add the two expresssion

= ( 3x + y)+ (-4x -2y)

Open bracket

=3x+y-4x-2y

collect like terms

=3x-4x+y-2y

=-x-y

Hence the result is (-x-y)